The use of GPS to evaluate activity profiles of elite women hockey players during match-play - Macutkiewicz, D.; Sunderland, C. (Journal of Sports Sciences, 2011)
The aim of the study was to assess the match-play activity patterns of elite women field-hockey players using a global positioning system (SPI Elite, GPSports, Fyshwick, Australia). The activity of 25 players was analysed for 13 international matches, totalling 158 player-match analyses. Overall mean playing time was 48 ± 4 min but this varied according to playing position (defenders: 56 ± 11 min; midfielders: 50 ± 10 min; forwards: 38 ± 7 min; P < 0.001, d = 0.57-1.92). In total, 55.5 ± 6.3% of match time was spent performing low-intensity exercise (standing: 5.8 ± 2.7%; walking: 49.7 ± 5.6%). Moderate-intensity exercise accounted for 38.1 ± 5.0% (jogging: 25.8 ± 3.5%; running: 12.3 ± 2.9%) of player match-time, with the remainder made up of high-intensity exercise (fast running: 4.9 ± 1.4%; sprinting: 1.5 ± 0.6%). Forwards spent more time performing moderate- (41.4%) and high-intensity (7.7%) exercise than defenders and midfield players (P < 0.001). This is the first study to use a global positioning system to assess the activity characteristics of elite female hockey players and demonstrate that these characteristics differ according to playing position. These differences are probably attributable to the ways in which substitution of players occurs.